A regional approach to reduce postoperative opioid prescribing in Ontario, Canada. (6th October 2022) - Jackson, Timothy D; Maeda, Azusa; Beath, Tricia; Ahmad, Nancy; Price-arsenault, Pierrette; Jia, Hui; Lam, Jonathan; Schramm, David
Abstract: Background : Opioid-related morbidity and mortality continue to rise in the province of Ontario. We implemented a provincial campaign to reduce the number of opioid pills prescribed at discharge after surgery in the Ontario Surgical Quality Improvement Network (ON-SQIN). Methods : Activities related to the provincial campaign were implemented between April 2019 and March 2020 and between October 2020 and March 2021. Self-reported data from participating hospitals were used to determine changes in postoperative opioid prescribing patterns across participating hospitals. Results : A total of 33 and 26 hospitals participated in the provincial campaign in the first and second year, respectively. During the first year of the campaign, the median morphine equivalent (MEQ) from opioid prescriptions decreased significantly in a number of surgical specialties, including General Surgery (from 105 [75–130] to 75 [55–107], P  < 0.001) (median, interquartile range) and Orthopedic Surgery (from 450 [239–600] to 334 [167–435], P  < 0.001). The median number of opioid pills prescribed at discharge per surgery also decreased significantly, from 25 (15–53) to 15 (11–38) for 1 mg hydromorphone ( P  < 0.001) and 25 (20–51) to 20 (15–30) for oxycodone ( P  < 0.001). The decrease in opioid prescriptions continued in the second year of the campaign. Conclusions : Our approach resulted in a significant reduction in the number of postoperative opioids prescribed across a number of surgical specialties. Our findings indicate that evidence-based strategies derived from a regional collaborative network can be leveraged to promote and sustain quality improvement activities.